New breeding material of winter rapeseed (Brassica napus L.) with increased yield and high oleic acid content in seed oil - A. A. Golova; L. A. Gorlova; S. G. Efimenko (Труды по прикладной ботанике, генетике и селекции)
Background. The development of rapeseed cultivars with higher oleic acid content in seed oil is an important goal of rapeseed breeding programs worldwide, but the yield of high-oleic lines and cultivars is lower than that of traditional high-yielding cultivars and hybrids. Obtaining winter rapeseed that would combine high oleic acid and yield indicators will allow agricultural producers to be more financially interested in growing high-oleic cultivars to increase the production of useful products.Materials and methods. The study involved S3 and S4 generation plants from crosses between lines from cvs. ‘Selegor’ and ‘Sarmat’ with normal oleic acid content (60–63%), and high-oleic lines VN-1844 and VN-1848 from a deep inbreeding generation (S14) containing 79–81% of omega-9. Agronomic assessment was carried out in the control nursery and the progeny evaluation nursery in 2023/2024. The fatty acid composition was measured on a MATRIX-I Bruker Optics device.Results. In 2023, the best lines were identified for their high yields (4.64–5.00 t/ha), high levels of oleic acid (78.1–80.2%) and oil (47.9–50.1%), a shortened growing season (by 2–6 days), and low glucosinolate content (13.0–17.6 mmol/g). Under the 2024 conditions, the best lines surpassed in their yield both the high-oleic cv. ‘Olivin’ (by 0.22–1.02 t/ha) and the reference cv. ‘Loris’ (by 0.05–0.70 t/ha). The recombinant lines were characterized by high levels of oleic acid (78.1–80.0%) and oil (49.6–51.6%), optimal content of glucosinolates (14.4–20.7 mmol/g), and a shortened growing season (by 1–6 days).Conclusion. The selected lines will be tested in nurseries in the framework of preliminary, competitive, and environmental variety trials, and used as parent components in the production of CMS hybrids.